A portrait of workplace discrimination in Italy: empirical evidence from a nationwide survey. Issue 1 (2nd September 2019) - Palumbo, Rocco; Manna, Rosalba
Abstract : Purpose: Workplace discrimination negatively affects the functioning of organizations. Scholars have generally focused their attention on specific forms of prejudiced treatment at work as well as on particular groups of discriminated employees. Conversely, studies investigating the multifacetedness of this phenomenon are sporadic. The purpose of this article is to contribute to the advancement of the scientific knowledge about workplace discrimination showing a full-fledged portrait of this phenomenon in Italy. Design/methodology/approach: Secondary data about self-reported experiences of workplace discrimination of a large sample of Italian people were collected and run in a logistic regression model. Five forms of discrimination at work were taken into account: prejudiced job design and work allocation; discriminatory use of promotion and awards; wage differentials; unjustified increased workload; and mismanagement of HRM instruments. Findings: More than a fifth of respondents perceived at least one form of workplace discrimination. Different types of prejudiced treatment were triggered by distinctive socio-demographic and work-related factors. People who were unemployed at the moment of the interview were consistent in claiming that they suffered from all the forms of workplace discrimination. Former employees who underwent a work-family conflict were more likely to suffer from iniquitous treatment at work. Research limitations/implications: The occurrence of workplace discrimination was not objectively assessed. Besides, since only Italian people were included in this study, the findings are not generalizable at the international level. Originality/value: This article provides some insights to inspire policy and management interventions intended to prevent and/or curb the occurrence workplace discrimination.